Ligustilide promotes apoptosis of cancer-associated fibroblasts via the TLR4 pathways. (January 2020) - Ma, Jing; Mei, Jie; Lu, Jia; Wang, Yuanyuan; Hu, Minghua; Ma, Fangli; Long, Hanan; Qin, Zhihai; Tao, Ning
Abstract: The goal of this research was to study the selective pro-apoptotic effect of ligustilide on prostate-cancer-associated fibroblast in the tumor microenvironment and the related molecular mechanisms. The effects of ligustilide on cancer-associated fibroblasts (CAFs) and normal fibroblasts (NFs) isolated from the prostate were determined by MTT assay. Flow cytometry and cellular immunofluorescence were used to detect the effects of ligustilide on the cell cycle and apoptosis. Western blotting was used to detect the expression of apoptosis-related proteins after the action of ligustilide on CAFs. In the investigation, ligustilide had a selective pro-apoptotic effect on prostate-CAFs. After ligustilide treatment, the proportion of CAFs in the G2-M phase of the cell cycle increased, and the expression of apoptosis-related proteins (p-P53, Bcl-2, Caspase9 and Cytochrome C) changed. Ligustilide blocks the CAF cell cycle and induces the apoptosis of CAFs.